2020
DOI: 10.1177/0300060520902608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbamazepine on the bone health of people with epilepsy: a systematic review and meta-analysis

Abstract: Importance: Increasing evidence indicates that carbamazepine (CBZ) treatment in people with epilepsy (PWE) has adverse effects on bone health. Objective: We conducted a meta-analysis to investigate the effect of CBZ on the bone health of PWE. Methods: Two independent reviewers systematically searched PubMed and EMBASE for eligible studies. Standard mean deviations (SMDs) with 95% confidence intervals were used as a measure to investigate the effect of CBZ on bone-related outcomes in PWE. Results: Levels of vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…This mechanism is primary linked to the use of phenobarbital, phenytoin, and carbamazepine. Several studies report the osteopenic effects of carbamazepine on bone metabolism (15)(16)(17)(18). On the other hand, several authors did not observe negative effects of carbamazepine therapy on vitamin D levels or biochemical markers of bone turnover (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is primary linked to the use of phenobarbital, phenytoin, and carbamazepine. Several studies report the osteopenic effects of carbamazepine on bone metabolism (15)(16)(17)(18). On the other hand, several authors did not observe negative effects of carbamazepine therapy on vitamin D levels or biochemical markers of bone turnover (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Meyer et al concluded that the molecule of lamotrigine shows good penetration into tumor tissues and therefore might be efficacious in brain tumor patients, and even, due to its excellent tolerability and auspicious safety profile, it might be considered as the first choice agent for treating seizures in these patients (22). Nevertheless, the unfavorable effects of LTG on bone, including bone loss, impaired growth in children, alterations in BMD, and elevated bone turnover markers, have been reported (16,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The association between carbamazepine monotherapy and BMD was also investigated in this study, and it was found that the use of this medication significantly decreased BMD, while no effect on serum osteocalcin levels was found [ 397 ]. However, no significant difference in BMD was found when comparing carbamazepine users to controls in a systematic review and meta-analysis investigating the effect of carbamazepine on bone health [ 399 ]. Furthermore, a decrease in femoral neck BMD after 1 year of treatment with phenytoin [ 398 ] and a greater rate of bone loss determined by BMD in users of phenytoin compared to non-users of ACs [ 400 ] was reported in previous literature.…”
Section: Non-osteoporotic Medications Fracture Risk and Bmdmentioning
confidence: 99%
“…Another issue that needs to be addressed in the long-term treatment is decreasing bone mineral density causing osteoporosis that can occur with several CYP P450-inducing antiepileptics, most frequently, however, with CBZ [ 107 ] inducing the metabolism of vitamin D [ 107 , 108 ]. Therefore, guidelines recommend prophylactic prescription of vitamin D [ 109 ] and regular checks of vitamin D levels as well as regular bone densitometry.…”
Section: Methodsmentioning
confidence: 99%